Formulation and In vivo studies of Clopidogrel by Self-Nanoemulsifying Drug Delivery System (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
A self-nano emulsifying drug delivery system (SNEDDS) has been explored to improve poorly water-soluble drug clopidogrel’s solubility and dissolution rate. Different formulations were prepared using oil, surfactant, and co-surfactant in varying ratios. From the ternary phase diagram resultant formulations were investigated for clarity, phase separation, drug content, % transmittance, globule size, freeze-thaw, in vitro dissolution studies, particle size analysis, and zeta potential. Based on particle size, zeta potential and dissolution profile, and other studies, F6 was the best formulation of clopidogrel SNEDDS. The particle size of the optimized SNEDDS formulation was found to be 5.2 nm, and zeta potential was found to be -29 mV which complies with the requirement of the zeta potential for stability. The % release from optimized SNEDDS formulation F6 was highest (98.93%) and faster than other SNEDDS formulations and pure drug substance (32%), indicating the influence of droplet size on the drug dissolution rate. FTIR data revealed no physicochemical interaction between drug and excipients. In vivo bioavailability studies were carried out on the optimized formulation (F6), mean time to attain peak drug concentration (Tmax) was 0.5 ± 0.53 and 1.5 ± 0.72 minutes for the optimized and pure drug, respectively, while means maximum drug concentration (Cmax) was 6.77 ± 1.73 ng/mL and 2.10 ± 0.39 ng/mL respectively. AUC0-α and AUC0-t for the optimized formulation were significantly higher (p<0.05) 20.5 ± 2.48 ng.h/mL than the pure drug 6.34 ± 1.73 ng h/mL, respectively. Thus, the results indicate clopidogrel with SNEDDS formulation may be used to improve solubility and dissolution rate for the effective management of heart disease.